Evaluation of physical activity among undergraduate students in Mogadishu Universities in the aftermath of COVID-19 restrictions - AL-Mhanna,Sameer Badri; Wan Ghazali,Wan Syaheedah; Mohamed,Mahaneem; Sheikh,Abdulrahman Mohammed; Tabnjh,Abedelmalek Kalefh; Afolabi,HafeezAbiola; Mutalub,Yahkub Babatunde; Adeoye,Azeez Omoniyi; Mohamed Nur,Mariam; Aldhahi,Monira I. (PeerJ, 2022)
Background International restrictions were enacted during the COVID-19 pandemic to limit social interaction and viral transmission. These measures had a negative impact on physical activity (PA), creating changes in students’ health and lifestyles. The present study aimed to evaluate the levels of PA among undergraduate students in three different universities in Mogadishu after the relaxation of COVID-19 lockdown using the international physical activity questionnaire-long version (IPAQ-L) and its potential associated factors. Methods This study is a multicentral study conducted at Somali International University, Horn of Africa University, and Daha International University. A total of 1,189 respondents were asked to answer the online questionnaire provided via a link shared using their social media. Results After COVID-19 restrictions approximately ≥ 150 minutes of PA per week was reported by 500 men (97.3%) and 652 women (96.6%) at work. While 7 (1.4%) of men and 20 (3%) of women participate in < 150 minutes each week, respectively. Furthermore, only seven (1.4%) of males and three (0.4%) of women reported to have not performed any PA at work. Conclusion The majority of the undergraduate students at the selected universities in Mogadishu were physically active after the relaxation of COVID-19 rules in Somalia. Such a high level of PA is a significant advantage to public health.
Keywords: Lockdown; Coronavirus disease; Exercise; Public health; Questionnaire